Cerebrospinal fluid amounts of HLA-G in dimeric form are strongly associated to patients with MRI inactive multiple sclerosis. (February 2016) - Fainardi, Enrico; Bortolotti, Daria; Bolzani, Silvia; Castellazzi, Massimiliano; Tamborino, Carmine; Roversi, Gloria; Baldi, Eleonora; Caniatti, Maria Luisa; Casetta, Ilaria; Gentili, Valentina; Granieri, Enrico; Rizzo, Roberta; et al.
Background: The relevance of human leukocyte antigen (HLA)-G in dimeric form in multiple sclerosis (MS) is still unknown. Objective: To investigate the contribution of cerebrospinal fluid (CSF) HLA-G dimers in MS pathogenesis. Methods: CSF amounts of 78-kDa HLA-G dimers were measured by western blot analysis in 80 MS relapsing–remitting MS (RRMS) patients and in 81 inflammatory and 70 non-inflammatory controls. Results: CSF amounts of 78kDa HLA-G dimers were more frequent in RRMS than in inflammatory ( p <0.01) and non-inflammatory controls ( p <0.001) and in magnetic resonance imaging (MRI) inactive than in MRI active RRMS ( p <0.00001). Conclusion: Our findings suggest that HLA-G dimers may be implicated in termination of inflammatory response occurring in MS.